Effects of prohexadione calcium spraying during the booting stage on panicle traits, yield, and related physiological characteristics of rice under salt stress - Huang,XiXin; Zheng,Dianfeng; Feng,Naijie; Huang,Anqi; Zhang,Rongjun; Meng,Fengyan; Jie,Yin; Mu,Baomin; Mu,Dewei; Zhou,Hang (PeerJ, 2023)
Prohexadione calcium (Pro-Ca), as a growth retardant, can effectively alleviate the damage of salt stress to plants. In order to explore the effects of NaCl stress on the physiological characteristics and panicle traits of rice plants as well as the alleviating effect of Pro-Ca at the booting stage, we performed pot experiments on two rice cultivars: conventional rice ‘Huanghuazhan’ and hybrid rice ‘Xiangliangyou900’. Rice plants were treated with 0.3% NaCl 48 hours after Pro-Ca (100 mg L−1) treatment to study the effects of Pro-Ca on the physiological characteristics of the leaves and panicles, as well as the panicle and yield traits of rice under salt stress. Our analysis indicated that NaCl treatment inhibited the morphological growth parameters and photosynthetic efficiency, destroyed the antioxidant defense systems of leaves and panicles, increased soluble protein and proline in both rice cultivars. Foliar application of Pro-Ca significantly increased the leaf area, uppermost internode length, panicle length, panicle weight, number of primary branches, number of grains per panicle, seed setting rate and yield under salt stress. Pro-Ca application significantly affected chlorophyll content, net photosynthetic rate (Pn), stomatal conductance (Gs), transpiration rate (Tr), and apparent mesophyll conductance (AMC) in NaCl-treated rice cultivars compared with NaCl treatment alone. Moreover, Pro-Ca also increased ascorbic acid (AsA) content, enhanced superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX) activity, and further increased the accumulation of soluble protein and proline in leaves and panicles. These results illustrated that foliar application of Pro-Ca at the booting stage could alleviate the damage caused by NaCl stress by regulating the physiological and metabolic processes of rice plants, thereby enhancing the stress resistance of the plants, increasing total rice yield in salt stress conditions.
Keywords: Prohexadione calcium; Salt stress; Rice; Booting stage; Panicle traits